TISSUE-BASED GENE EXPRESSION FOR PROGNOSIS OF PROSTATE CANCER LOCAL STAGE - Yuri Tolkach; Markus Kuczyk; Axel Merseburger; Jürgen Serth; Thomas Herrmann; Florian Imkamp (Вестник урологии, 2015)
The aim of our study was the evaluation of the prognostic role of 42 genes, which were shown to be relates to prostate cancer aggressiveness in previous studies. We have included 28 patients in the study, 19 with localized prostate cancer according to final pathology after radical prostatectomy (pT2a-2c) and 9 patients with locally advanced prostate cancer (pT3a-b). Analysis of the gene expression (PCR) revealed 6 genes with differential expression in tumor tissues of patients from 2 aforementioned groups: GOLM1, GBX2, XPO6, SSTR1, TOP2A and CDCA5. We have created a prognostic model of the pT-stage based on the expression of these 6 genes, which proved to be accurate in 75% of the included cases.